Identifying Components of Virtual Learning Culture in Higher Education Institutions - Mirkizadeh Mohammadabad, Mahnaz; Jabbary, Negin; Esmaeilnia Shirvani, Kambiz (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The objective of this study is to identify the key components essential for fostering a virtual learning culture in higher education institutions. By understanding these components, the study aims to provide insights that can help institutions enhance the effectiveness and inclusiveness of their virtual learning environments. Methodology: This qualitative research utilized semi-structured interviews to gather in-depth insights from 12 experts in higher education and virtual learning. Participants were selected using purposive sampling based on their extensive experience and knowledge in the field. Data were collected until theoretical saturation was achieved and analyzed using NVivo software, which facilitated the organization, coding, and interpretation of the qualitative data. Findings: The analysis revealed several critical components categorized into structural and behavioral factors. Structural factors included software and hardware infrastructure, design and management of virtual learning interactions, virtual learning environment setup, virtual learning development, and operational support capability. Behavioral factors comprised culture building, individual attitudes, and learner motivation. The study highlighted the importance of robust digital infrastructure, effective teacher-student interactions, cultural inclusiveness, and the provision of continuous support and empowerment for both educators and learners. Conclusion: The findings underscore the multifaceted nature of virtual learning culture in higher education, emphasizing the need for comprehensive strategies that address both structural and behavioral components. Institutions must invest in the necessary infrastructure, foster effective interactions, provide empowerment courses, and build a supportive culture to create an engaging and inclusive virtual learning environment. These insights can guide the development of policies and practices that enhance the quality and effectiveness of virtual learning, ultimately improving educational outcomes for all students.